Effect of Dilute Acid and Alkaline Pretreatments on Enzymatic Saccharfication of Palm Tree Trunk Waste for Bioethanol Production - Kusmiyati Kusmiyati; Sakina Tunissa Anarki; Sabda Wahyu Nugroho; Reistu Widiastutik; Hadiyanto Hadiyanto (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
The sugar palm tree (Arenga pinnata) was abundant in Indonesia and has high cellulose contents for bioethanol production. However, the lignin content was the major drawback which could inhibit saccharification enzymes and therefore removing the lignin from the biomass is important. This paper evaluated the effects of pretreatments  using nitric acid (HNO3) and ammonium hydroxide (NH4OH) at 2 to 10% (v/v) on reducing sugar and ethanol contents and compared with the effects of steam pre-treatment. The pretreated samples were hydrolyzed using cellulase enzymes at pH 5.0 with a substrate concentration of 10% (w/v) for 24 to 72 h at 50 °C. Subsequent assessments of enzymatic saccharification following pre-treatment with 10% (v/v) HNO3 showed maximum reducing   and total sugar contents in palm tree trunk waste of 5.320% and 5.834%, respectively, after 72 h of saccharification. Following pretreatment with 10% (v/v) of NH4OH, the maximum reducing and total sugar contents of palm tree trunk waste were 2.892% and 3.556%, respectively, after 72 h of saccharification. In comparison, steam pretreatments gave maximum reducing sugar and total sugar contents of 1.140% and 1.315% under the same conditions. Simultaneous saccharification and fermentation (SSF) was conducted at 37 °C (pH 4.8) and 100 rpm for 120 h using 10% (v/v) Saccharomyces cerevisiae and cellulase enzyme with a substrate concentration of 10% (w/v). The result showed the highest ethanol content of 2.648% was achieved by using 10% (v/v) HNO3. The use of 10% (v/v) NH4OH gained a yield of 0.869% ethanol while the steam pretreatment could obtained 0.102% ethanol.